Carbon concrete- the creative building material- its properties and performance indicators in strengthening the elements of structures: الخرسانة الكربونية – مادة البناء الإبداعية – خصائصها ومؤشرات أدائها في تدعيم عناصر المنشآت - Zuhair Amer (مجلة العلوم الهندسية و تكنولوجيا المعلومات, 2022)
Construction and restoration operations have developed rapidly since the beginning of this century. This development coincided with the trend of towards developing and discovering new building materials that meet the aspirations and needs of those interested across all engineering fields. One of the most important building materials currently being developed is carbon concrete, in which carbon is used for reinforcement instead of steel, which has been the material in use until today. Due to the many advantages of using carbon concrete whether in building new structures or in repairing, strengthening and consolidation of existing buildings, this innovative material will replace conventional reinforced concrete in the near future. This study aims to shed light on carbon concrete and present the latest findings of scientific research on this material and its production and use techniques, whether in modern buildings under construction or in existing buildings for the purpose of repair and rehabilitation. It also aims in its experimental part to study the effects of reinforcement using carbon concrete on the behavior of implemented concrete elements (for example, column elements) by changing many parameters. This research paper presents the characteristics and components of carbon concrete, its manufacturing methods and areas of use, in addition to the advantages and disadvantages of the new carbon concrete through a brief overview in order to introduce this creative building material in the Arab sector and encourage its use as an alternative to reinforced concrete. However, there is still an urgent need for scientific research into the details of carbon concrete. Only then can standardized and complete concepts be presented for their practical use and, above all, the code version to be followed when utilizing them.